The art of the possible : diplomatic alternatives in the Middle East - Reisman, W. Michael (William Michael), 1939- (Princeton legacy library., 1970)
The Art of the Possible takes a hard look at the present play of forces in the Middle East. In full awareness of the historical, political, social, and psychological dimensions of the enmities of the region-and its most critical flashpoint, the Arab- Israeli conflict-it seeks realistic answers to the question ""What can be done?"" For each of the immediate foci of conflict, the author develops and proposes a workable plan: for the Sinai Peninsula, the establishment of a Sinai Development Trust; for the West Bank of the Jordan River, the creation of a Palestinian state; for the Golan Heights,